Seletividade de glyphosate isolado ou em misturas para soja RR - Alonso, Diego Gonçalves (2008)
Although glyphosate-resistant soybean has widened the options of weed chemical control in the crop, the evaluation of selectivity for herbicide mixtures is still deficient. Aiming at studying the selectivity of glyphosate isolated or in mixture with other herbicides applied at postemergence for glyphosate-resistant soybean (cv. CD 214 RR), four experiments were conducted without weed interference using two-fold checks. The experiments were constituted of eleven treatments each and the application period was different for each of them. In experiment I, the treatments used (rates at g a.i. ha-1 or g a.e. ha-1) were: isolated glyphosate at 720, 960, 1200 and 1440 and glyphosate mixtures (960) with cloransulam-methyl (30.24), fomesafen (125), lactofen (72), chlorimuron-ethyl (12.5), flumiclorac-pentyl (30), bentazon (480) and imazethapyr (80) at single application when the soybean was at V2 to V3 stage. In experiments II to IV, the treatments were constituted of two applications of herbicides. The first was carried out at V1 to V2 stage and the second at V3 to V4 stage (15 days after the first application). For experiment II, the treatments were constituted of isolated glyphosate at 720/480, 960/480, 1200/480 and 960/720 and in mixtures at 720 with the same herbicides and rates of experiment I in the first application. The second glyphosate application was at 480. Experiment III was constituted of isolated glyphosate on both applications (720/480, 720/720, 720/960 and 720/1200) and also isolated in the first sequence at 720 and in mixtures at 480 with the same herbicides, at the same rates of experiment I in the second sequence. For experiment IV, the treatments were constituted of sequential application of isolated glyphosate at 720/480, 720/720, 960/960 and 1200/1200 and in mixtures at 720 in the first application and 480 in the second with cloransulam-methyl (15.12), fomesafen (62.5), lactofen (36), chlorimuron-ethyl (6.25), flumiclorac-pentyl (15), bentazon (240) and imazethapyr (40). Phytointoxication (% and EWRC), stand, height, soil cover by crop canopy, number of pods per plant, mass of 100 grain and grain yield evaluations were carried out. We verified that all treatments caused injuries in RR soybeans independently of rates and periods of applications. Such injuries varied in degree and persistence. It was also possible to notice that mixtures applications at earlier phases of the RR soybean cycle presented lower potential of yield reduction, showing higher selectivity to the crop. The glyphosate+lactofen mixture at 960+72 applied at a single rate at V2 to V3 stage, the sequential application of glyphosate/glyphosate+lactofen (720/480+72) at V1 to V2/V3 to V4 stages, and also the sequential application of glyphosate/glyphosate+bentazon (720/480+480) at V1 to V2/V3 to V4 stages promoted significantly yield reduction and demonstrated no selectivity to this cultivar.